Improving Technology to Diagnose Tuberculous Meningitis: Are We There Yet? - Ssebambulidde, Kenneth; Gakuru, Jane; Ellis, Jayne; Cresswell, Fiona V.; Bahr, Nathan C. (Frontiers in Neurology, 2022)
Diagnosis of tuberculous meningitis (TBM) remains challenging due to a paucity of high-performance diagnostics. Even those which have reasonable sensitivity are not adequate to ‘rule-out’ TBM. Therefore, a combination of clinical factors alongside microbiological, molecular and radiological investigations are utilized, depending on availability. A low threshold to start empiric therapy in the appropriate clinical scenario remains crucial for good outcomes in many cases. Herein we review the current TBM diagnostics landscape with a focus on limitations frequently encountered such as diagnostic test performance, cost, laboratory infrastructure and clinical expertise. Though molecular technologies, particularly GeneXpert MTB/Rif Ultra, have been a step forward, diagnosis of TBM remains difficult. We also provide an overview of promising technologies including cerebrospinal fluid (CSF) lactate, a new lipoarabinomannan test (FujiLAM), metagenomics next generation sequencing and transcriptomics that may further improve our TBM diagnostic capacity and lead to better outcomes.